Strontium isotope investigation of ungulate the Pleistocene Paleo-Agulhas Plain of the greater South Africa - Copeland, S; Cawthra, H; Fischer, E; Lee-Thorp, J; Cowling, R; Le Roux, P; Hodgkins, J; Marean, C (Elsevier, 2016)
Middle Stone Age sites located within the Greater Cape Floristic Region on the South African southern coast have material culture with early evidence for key modern human behaviors such as projectile weaponry, large animal hunting, and symbolic behavior. In order to interpret how and why these changes evolved, it is necessary to understand their ecological context as it has direct relevance to foraging behavior. During periods of lowered sea level, a largely flat and vast expanse of land existed south of the modern coastline, but it is now submerged by higher sea levels. This exposed area, the Paleo-Agulhas Plain, likely created an ecological context unlike anything in the region today, as evidenced by fossil assemblages dominated by migratory ungulates. One hypothesis is that the Paleo-Agulhas Plain supported a migration ecosystem of large grazers driven by summer rainfall, producing palatable forage during summer in the east, and winter rainfall, producing palatable forage during winter in the west. Alternatively, ungulates may have been moving from the coastal plain in the south to the interior north of the Cape Fold Mountains, as observed for elephants in historic times. In this study, we assess ungulate movement patterns with inter- and intra-tooth enamel samples for strontium isotopes in fossil fauna from Pinnacle Point sites PP13B and PP30. To accomplish our goals we created a bioavailable 87Sr/86Sr isoscape for the region by collecting plants at 171 sampling sites and developing a geospatial model. The strontium isotope results indicate that ungulates spent most of their time on the Paleo-Agulhas Plain and avoided dissected plain, foothill, and mountain habitats located more than about 15 km north of the modern coastline. The results clearly exclude a north-south (coastal-interior) movement or migration pattern, and cannot falsify the east-west movements hypothesized in the south coast migration ecosystem hypothesis.